THE EFFECT OF OYSTER SHELL IN COMMERCIAL RATIONS ON PERCENTAGE OF EXTERNAL OFFAL OF ISA BROWN CHICKEN 104 WEEKS - R. F., Ginarwansyah; Dewi, G. A. M. K.; Wiraparta, M. (Jurnal Peternakan Tropika; Vol 11 No 2 (2023): Vol. 11 No. 2 Tahun 2023; May - August, 2023)
This study aimed to determine the effect of giving oyster shell flour in commercial rations on the percentage of external offfal of Isa Brown chickens aged 104 weeks. The design used was a completely randomized design (CRD) consisting of 4 treatments and 5 replications and each replication consisted of 5 chickens, a total of 100 chickens used Isa Brown. The treatments given were, A: without giving clam shell flour, B: giving 1% clam shell flour, C: giving 2% clam shell flour, and D: giving 3% clam shell flour. The variables observed were the percentage of the head, the percentage of the neck, the percentage of the legs, the percentage of blood, and the percentage of fur. The results showed that the percentage of Isa Brown chicken feathers aged 104 days in treatments B, C, and D obtained results of 5.17, 4.27% and 4.82%, respectively, significantly lower (P0.05). Based on the results of the study, it can be concluded that giving oyster shells as much as 1%, 2% and 3% reduced the percentage of feathers, but in the control, 1%, 2%, and 3% did not affect the percentage of head, neck, blood, and feet of aged Isa Brown chickens. 104 weeks. Keywords: Isa Brown's chicken. external offal, oyster shell flour